Injection molding with an additive manufactured tool. Issue 9 (25th July 2019) - Simpson, Patrick; Zakula, Autumn D.; Nelson, Jake; Dworshak, Jeremy K.; Johnson, Eric M.; Ulven, Chad A.
Abstract : This study examines the viability of using additively manufactured injection molding tools for short run proof‐of‐concept plastic parts by assessing the quantity and quality of molded parts. Prototyping injection molded parts traditionally can be very expensive, but with improved additive manufacturing materials and techniques such costs could be reduced. To prove this, plastic tools were made by using PolyJet and Fused Deposition Modeling out of Digital ABS, FullCure 720, and ULTEM 1010 materials in this study. The test tools were then compared to the standard P20 metal tool by molding acetal, polycarbonate (PC), and polypropylene (PP) in each tool type. The molded parts were analyzed for processing effects on part shrink, physical, and mechanical properties. Testing concluded that parts molded with additively manufactured tools performed comparably to parts made on a P20 tool. However, the quantity of satisfactory parts molded in acetal and PC were consistent with the literature at 10–100 parts. Conversely, molding in PP suggested that processing with additive manufactured tools could exceed 250 parts. POLYM. ENG. SCI., 59:1911–1918, 2019. © 2019 Society of Plastics Engineers